Post-covid-19 rehabilitation: a case report (Research, Society and Development, 2022)
Introduction: Covid-19 affected a lot of people leaving sequels, both in patients who had the mildest and more severe cases. General objective: Reporting a patient's experience in post-Covid-19 rehabilitation. Methodology: this is a qualitative study, of the case report type, about the rehabilitation of a patient after Covid-19. Data collection was performed by interviewing the patient via videoconferencing, respecting the protocols in force due to the pandemic at the time. To facilitate the participant's interaction at the time of data collection, and with the patient's consent, the interview was recorded. Since this is a new pathology and with very little evidence about Covid-19, bibliographic articles selected from Google Scholar and SciELO published between 2019 and 2022 were used to support the information obtained in the interview, to understand and substantiate the report. Discussion: According to the Ministry of Health (2020), rehabilitation services are a therapeutic process, not characterizing an area of professional exclusivity, but a proposal for multidisciplinary action. Conclusion: It is expected that this research be of great importance for people who have had or who will have sequels of Covid-19 to have a quality rehabilitation process.